2001
DOI: 10.1590/s0036-36342001000600009
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene and restraint of pigs is associated with absence of Taenia solium cysticercosis in a rural community of Mexico

Abstract: Vázquez-Flores S, Ballesteros-Rodea G, Flisser A, Schantz PM. La higiene y el confinamiento de cerdos están asociados con la ausencia de cisticercosis por Taenia solium en una comunidad rural de México. Salud Publica Mex 2001;43:574-576. El texto completo en inglés de este artículo también está disponible en: http://www.insp.mx/salud/index.html

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In contrast, in Cameroon there was no association of infection in pigs in households without a latrine when compared to those with a latrine [24]. Another study in Mexico showed that latrines were available in the majority of households (91%) and none of the 53 pigs studied showed cysts in the tongue or antibodies against T. solium in western blot assays [25].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, in Cameroon there was no association of infection in pigs in households without a latrine when compared to those with a latrine [24]. Another study in Mexico showed that latrines were available in the majority of households (91%) and none of the 53 pigs studied showed cysts in the tongue or antibodies against T. solium in western blot assays [25].…”
Section: Discussionmentioning
confidence: 91%
“…In addition to the need for improvement of infrastructure is the need to provide appropriate information to communities. Education in combination with other interventions has been shown to have the greatest impact on lowering levels of these diseases [27] with one of the earliest reported examples in a rural community in Mexico [25], [27]. A more recent example tested the efficacy of teaching methods in Kenyan farmers to prevent human epilepsy caused by neurocysticercosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…In Coapeche, Veracruz, where swine cysticercosis was ascertained by western blot, none of the 53 pigs studied had antibodies or cysticerci. Latrines were present in 91% of houses and pigs were kept in restrained areas, demonstrating that adequate basic sanitary conditions and pig breeding practices are effective and practical to control T. solium in rural communities [58]. High standards of meat inspection and proper disposal of infected pig carcasses will also aid in preventing infected pigs from entering the food chain.…”
Section: Risk Factors and Intervention Trialsmentioning
confidence: 99%
“…Neurocysticercosis is the most common cause of seizures in areas where the disease is endemic [24]. Risk factors for high rates of cysticercosis include poor sanitary conditions and lack of pork inspection prior to marketing [24,25]. Seizures frequently recur [26].…”
Section: Taeniasismentioning
confidence: 99%